ANALYSIS OF HUMAN RESOURCES DEVELOPMENT OF POULTRY FARMERS IN IMPROVING WORK PRODUCTIVITY THROUGH CORE PLASMA PARTNERSHIP WITH PT SUPER UNGGAS JAYA IN MUARA ENIM REGENCY - Agustian, Wiwin; Purnama, Des Randi (Jurnal Ecoment Global, 2024)
Abstract. Objective : This research is to analyze how the form of Human Resource Development of Poultry Farmers in Increasing Work Productivity Through Core Plasma Partnerships with PT Super Unggas Jaya in Muara Enim Regency.   Design/Method/Approach: This research uses a qualitative method. The data collection technique used is by interview, in which the informants are poultry farmer employees who participate in the training, namely 6 people, in the data analysis process the researcher uses qualitative descriptive analysis with the stages of data collection, data reduction, data presentation, drawing conclusions.   Result : Human Resource Management at PT Super Unggas Jaya focuses on developing the quality of partner farmers, in this case human resource development is carried out routinely in the form of training. This study uses a qualitative descriptive method, the data used is primary data, in data collection using informants. From the results of the discussion and analysis, it can be explained that with the development of human resources through partnerships with PT Super Unggas Jaya, poultry farmers gain very useful skills so that the productivity of the farmers' work becomes better, with the increasing productivity of the farmers' work, it is expected that the results obtained can be better than when raising livestock independently. This is in accordance with the existing theory explaining that the purpose of training and development is to increase individual self-awareness, individual skills in certain areas of expertise, and to increase individual motivation in doing work satisfactorily so that work productivity can increase. Pratical/policy implication : The implementation of development and training by PT Super Unggas Jaya for its partners should be maintained and if possible can be improved because it is good enough and in accordance with the needs of farmers Keywords: Poultry Farmers, Work Productivity, Core Plasma Partnership